Acute dermatomyositis associated with a staphylococcal infection. Issue 674 (December 1981) - Heagerty, A. M.; Byrom, N. P.; Cookson, J. B.
Abstract : A case is reported of dermatomyositis developing in a woman with staphylococcal osteomyelitis. After treatment for the infection, the dermatomyositis resolved and no other cause for it has been found. Dermatomyositis has not previously been described in conjuction with a staphylococcal infection.